PELAKSANAAN PERLINDUNGAN KONSUMEN DI INDONESIA - Niru Anita Sinaga; Nunuk Sulisrudatin (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2015)
Everyone either alone or jointly surely be the consumers to a particular product or service. That requires the legal protection of the parties in a balanced manner both at the time prior to the transaction and/or at the time after the transaction. Generally known there are four basic consumer rights that must be protected, namely: the right to safety, the right to information, right to vote and the right to be heard. In practice the legal protection of consumers still poses various problems that affected various factors, among others: relating to the legal structure, the substantive law and legal culture and bureaucratic apparatus. For addressing these problems, it is necessary to look for solutions, among others: As soon as possible to revise the existing UUPK; law to be formed is responsive law; and the seriousness of law enforcement to monitor, process and resolve any violations with penalties/sanctions were firm and commensurate so deterrent to those who commit violations